Evolution of the kidney–cancer connection. Issue 2 (June 2019) - Perazella, Mark A; Workeneh, Biruh; Chen, Sheldon
Over the past decade, Onco-Nephrology has emerged as an important sub-field of not only nephrology and oncology but also hematology, urology, critical care medicine, clinical pharmacology, and palliative care medicine. This nexus reflects the unique connection that exists for kidney disease and cancer in all of clinical medicine. As noted, Onco-Nephrology combines the knowledge and skills of a number of specialty groups that span all areas of medicine. In this issue of the Journal of Onco-Nephrology, a series of papers addressing the various forms of kidney disease that develop in patients with cancer and its therapy is presented as part of the Onco-Nephrology Highlights section. These papers are based on the Onco-Nephrology Symposium that took place at MD Anderson Cancer Center in 2018. We hope you find these six papers educational and practical as you evaluate and treat patients with cancer and kidney disease in your clinical practice.